Biosynthesis of Silver Nanoparticles by Aspergillus terreus: Characterization, Optimization, and Biological Activities - Lotfy, Walid A.; Alkersh, Basma M.; Sabry, Soraya A.; Ghozlan, Hanan A. (Frontiers in Bioengineering and Biotechnology, 2021)
In this study, mycelial filtrate of Aspergillus terreus BA6 was used to reduce AgNO3 to form silver nanoparticles (AgNPs). The effect of seven independent variables on AgNPs diameter was studied by applying design of experiments (DOE). At optimal conditions, the diameter of AgNPs was reduced by approximately 26.7% compared to the basal culture condition and AgNO3 concentration was found to be the most significant factor affecting the diameter of AgNPs. A. terreus nano-Ag was characterized using UV-visible spectroscopy, transmission electron microscopy, energy dispersive X-ray (EDX), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and Zeta potential. The maximum UV absorption was obtained at 420 nm and the microscopic results showed particles having narrow size distribution ranged from 7 to 23 nm. XRD pattern of AgNPs revealed four diffraction peaks of metallic silver and the EDX spectrum showed a strong signal attributed to Ag nano-crystals. AgNPs mycofabricated by A. terreus showed potent minimum inhibitory concentration (MIC) and broad minimum bactericidal/fungicidal concentration (MBC/MFC) against 12 reference microorganisms. The MIC and MBC/MFC values of AgNPs were 0.312 to 1.25 µg/ml and 0.625 to 10 µg/ml, respectively. Nevertheless, AgNPs did not demonstrate any antagonistic activity against Coxsackie B virus. The in vitro cytotoxicity of the mycosynthesized AgNPs showed significant antitumor activity against adenocarcinoma epithelial cells from human breast cancer (Mcf-7) cell line with an inhibitory concentration (IC50) of 87.5 µg/ml.